The Identification of Mercury in The Urine of Night Cream Users in Midwifery Program Abdurrab University - Sepriyani, Harni; Sidoretno, Wahyu Margi; Elfia, Mega (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2021)
White and bright skin is everyone's dream. Many women who do facial skin care in order to obtain healthy facial skin and attractive appearance. Facial skin care that is mostly done is the use of facial whitening creams. Face whitening cream is believed to be able to remove or lighten black spots on facial skin. Whitening cream that is often used is a night cream. Some of the night creams sold have not received permission from National Agency of Drug and Food Control of Indonesia. Usually these creams contain heavy metals, such as mercury. Mercury is toxic which when exposed and absorbed by the body can cause loss of enzyme ability in the body to cancer. The purpose of this study was to determine the presence or absence of mercury in the night cream and urine of night cream users at Abdurrab University Midwifery Study Program students. The method of this research is a qualitative examination on samples of night cream and urine used KI reagent. The results showed that the night cream sampled gave a positive test result and the urine of night cream users gave a negative test result. The conclusion of this study is that the night cream sampled contained mercury and the urine of night cream users did not contain mercury.